2010
DOI: 10.1038/cdd.2010.105
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 downregulation by pro-inflammatory cytokines and palmitate is an early event contributing to β-cell apoptosis

Abstract: Pancreatic b-cell apoptosis is a key feature of diabetes mellitus and the mitochondrial pathway of apoptosis is a major mediator of b-cell death. We presently evaluated the role of the myeloid cell leukemia sequence 1 (Mcl-1), an antiapoptotic protein of the Bcl-2 family, in b-cells following exposure to well-defined b-cell death effectors, for example, pro-inflammatory cytokines, palmitate and chemical endoplasmic reticulum (ER) stressors. All cytotoxic stresses rapidly and preferentially decreased Mcl-1 prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
135
1
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 112 publications
(151 citation statements)
references
References 42 publications
(84 reference statements)
10
135
1
5
Order By: Relevance
“…1). This is paralleled by the decrease of two other important anti-apoptotic proteins: BCL-2 and MCL-1 [28], and by the increase in expression/activation of the BH3-only proteins PUMA and BIM [30,31]. Activation of the BH3-only proteins results in BAX translocation to the mitochondria, outer mitochondrial membrane permeabilisation, cytochrome c release, caspase activation and consequently beta cell apoptosis [9,28,32].…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1). This is paralleled by the decrease of two other important anti-apoptotic proteins: BCL-2 and MCL-1 [28], and by the increase in expression/activation of the BH3-only proteins PUMA and BIM [30,31]. Activation of the BH3-only proteins results in BAX translocation to the mitochondria, outer mitochondrial membrane permeabilisation, cytochrome c release, caspase activation and consequently beta cell apoptosis [9,28,32].…”
mentioning
confidence: 99%
“…Activation of the intrinsic apoptotic pathway is a key event in cytokine-mediated beta cell apoptosis [7,32,33], and overproduction of BCL-2 [34], BCL-XL [35] and MCL-1 prevents cytokine-induced apoptosis in vitro [28]. In vivo experiments, however, have shown that BCL-XL overproduction induces beta cell dysfunction [35], while increased production of BCL-2 is not sufficient to prevent autoimmune destruction of beta cells [36].…”
mentioning
confidence: 99%
See 3 more Smart Citations